Analisis Hasil Uji Sensitivitas Bakteri pada Ulkus Penderita Diabetes Melitus Tipe 2 di Salah Satu Rumah Sakit Yogyakarta - Fadhilah Zalfa Cahyaningrum; Dhiah Novalina; Monika Putri Solikah (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Diabetic ulcers are a condition that occurs in individuals suffering from diabetes mellitus due to damage to the nerves and peripheral arteries, leading to wound infections and damage to the skin tissue. The focus of this research is to determine the prevalence by gender, the types of bacteria that infect diabetic ulcers, and the patterns of antibiotic sensitivity at a hospital in Yogyakarta in 2024. This research employs a descriptive analytic design using a cross-sectional approach. The sampling technique uses total sampling, selecting all members of the population who meet inclusion and exclusion criteria. The data for this study were obtained from medical records during the period from January 1st to December 31st, 2024, with a total sample size of 86 diabetic ulcer patients. Of these patients, 53 are male and 33 are female who suffer from Type 2 Diabetes Mellitus with complications of diabetic ulcers. In addition, this research found 26 types of bacteria, where gram-negative bacteria are more dominant with 51 samples, while gram-positive bacteria amount to 35 samples. The most dominant type of gram-negative bacteria detected is Escherichia coli, while the most commonly identified gram-positive bacteria is Staphylococcus aureus. The antibiotics that are sensitive to gram-negative bacteria are meropenem, cefepime, and chloramphenicol. Meanwhile, the effective antibiotics against gram-positive bacteria are linezolid, gentamicin, and ciprofloxacin.